Impaired Neurodevelopmental Genes in Slovenian Autistic Children Elucidate the Comorbidity of Autism With Other Developmental Disorders - Krgovic, Danijela; Gorenjak, Mario; Rihar, Nika; Opalic, Iva; Stangler Herodez, Spela; Gregoric Kumperscak, Hojka; Dovc, Peter; Kokalj Vokac, Nadja (Frontiers in Molecular Neuroscience, 2022)
Autism spectrum disorders (ASD) represent a phenotypically heterogeneous group of patients that strongly intertwine with other neurodevelopmental disorders (NDD), with genetics playing a significant role in their etiology. Whole exome sequencing (WES) has become predominant in molecular diagnostics for ASD, by considerably increasing the diagnostic yield. However, the proportion of undiagnosed patients still remains high due to complex clinical presentation, reduced penetrance, and lack of segregation analysis or clinical information. Thus, reverse phenotyping, where we first identify a possible genetic cause and then determine its clinical relevance, has been shown to be a more efficient approach. WES was performed in 147 Slovenian pediatric patients with suspected ASD. Data analysis was focused on identifying ultra-rare or “single event” variants in ASD-associated genes, and further expanded to NDD-associated genes. Protein function and gene prioritization were performed on detected clinically relevant variants to determine their role in ASD etiology and phenotype. Reverse phenotyping revealed a pathogenic or likely pathogenic variant in ASD-associated genes in 20.4% of patients, with subsequent segregation analysis indicating that 14 were de novo variants and one a presumed compound heterozygous. The diagnostic yield was further increased by 2.7%, by analysis of ultra-rare or “single event” variants in all NDD-associated genes. Protein function analysis established that genes in which variants of unknown significance (VUS) were detected, were predominantly the cause of intellectual disability (ID), and in most cases, features of ASD as well. Using such approach, variants in rarely described ASD-associated genes such as SIN3B, NR4A2, and GRIA1 were detected. By expending the analysis to include functionally similar NDD genes, variants in the KCNK9, GNE, and other genes were identified. These would be probably have been missed by classic genotype-phenotype analysis. Our study thus demonstrates that in ASD patients, analysis of ultra-rare or “single event” variants obtained with by WES with the inclusion of functionally similar genes, and reverse phenotyping, we obtained a higher diagnostic yield despite limited clinical data. The present study also demonstrates that most of the causative genes in our cohort were involved in the syndromic form of ASD, and confirms their comorbidity with other developmental disorders.